Hypermobility Among Adolescents and the Association With Spinal Deformities: A Large Cross-Sectional Study - Hershkovich, Oded; Gordon, Barak; Derazne, Estela; Tzur, Dorit; Afek, Arnon; Lotan, Raphael (Journal of the American Academy of Orthopaedic Surgeons. Global research & reviews, 2024)
Introduction:Adolescent idiopathic scoliosis and Scheuermann kyphosis are common spinal deformities (SD) among adolescents. The potential link between hypermobility and SD is a topic of debate. We aimed to investigate the prevalence of hypermobility and its association with SD.Methods:A cross-sectional analysis of records of 17-year-old subjects who were recruited into mandatory military service was conducted. Study population comprised 1,220,073 subjects. Prevalence rates were calculated for hypermobility and different categories of SD by severity, studying the strength of the association between hypermobility and SD.Results:Of 1,220,073 subjects, 0.0111% exhibited hypermobility. Spinal deformities were identified in 10.5% of subjects. Specifically, 7.9% had mild SD, 2.4% had moderate SD, and 0.1% had severe SD. The overall association between hypermobility and SD showed an odds ratio of 2.31 (P < 0.001). Subgroup analyses revealed ORs of 1.226 (P = 0.041) for mild deformities, 5.783 (P < 0.001) for moderate deformities, and 4.01 (P = 0.002) for severe deformities. The association was stronger for moderate and severe SD.Conclusions:This study establishes a notable association between hypermobility and SD among adolescents. The findings highlight the importance of understanding this relationship, which could contribute to advancements in comprehending SD development. Additional research is warranted to expand upon these findings.